(untitled) (Journal of the College of Basic Education, 2023)
The study aimed to prepare skill exercises using the motor response system in developing some motor abilities, as well as preparing exercises on the (A.P.R.D) device to develop some motor abilities in football tennis, as well as identifying the effect of these exercises in developing some motor abilities in football tennis. The researcher hypothesized several Hypotheses, including the presence of statistically significant differences between the results of the pre and posttests in all the research variables, as the researcher chose the players of the Football City Football Tennis Academy for the year 2022-2023, and their number was (35) players as a community for his research. The other is a control, and the percentage of the sample to the community was (57.14%). Skills exercises were applied to the experimental group with auxiliary tools, which consisted of an innovative device, which is the device (A.P.R.D.) 90) minutes after that, post tests were conducted for motor abilities in football tennis. The s.p.s.s statistical bag system was used in the process of processing the results of the pre and posttests. The researcher reached a number of conclusions, the most important of which was that the exercises prepared and designed by the researcher were effective in developing the motor abilities of the research sample. applied to it and recommended taking the results of this study and benefiting from them in developing a football tennis curriculum for academic players and national teams in football tennis.